Pengembangan Aplikasi Penjualan Berbasis Web Studi Kasus: Rajakom - Rizal Abidin; Harya Bima Dirgantara (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of the research conducted is to develop a website-based sales system created for Rajakom Stores so that Rajakom Stores can promote products, store branding to expand market share, increase sales in the marketplace and assist customers in ordering products. The software development method used in this research is the Rational Unified Process (RUP) and the software modeling uses the Unified Modeling Language (UML). The result of this research is a website-based sales application system. Based on the results of black box testing, the features contained in the sales system were successfully created because they functioned and were used properly.